Internal hernia after an open gastrectomy: an unusual treatment approach and a systematic review of the literature - Cherchi, Vittorio Alessandro; Aveni, Giada; Clocchiatti, Lucrezia; Andriani, Adelaide; Intini, Sergio Giuseppe; Terrosu, Giovanni (Acta Biomedica Atenei Parmensis, 2023)
Internal hernia (IH) is a serious complication that can occur after both laparoscopic and open surgery for the treatment of gastric cancer; the transverse colon and mesocolon, act as a natural partition between stomach and the small intestine and, once any type of gastrojejunal anastomosis is constructed, a potential space for internal hernia is created. We present the case of a 68-year-old patient diagnosed with intestinal ischemia due to an IH in the site of the jejunojejunostomy after an open gastrectomy for gastric cancer, treated with negative wound pressure therapy (NWPT) on open abdomen (ABTHERATM dressing)